Bank's Legal Responsibility in Detecting Shadow Controller-Related Beneficial Owner - Wawan Zulmawan; Daniel Johnson Goenawan; Marchello Putra Toding Palilli; Ramdhan Mahardika Nasyith; Muhamad Naufal Rionatadiraja; Reyzel Yandika Lim; Triswer Triswer (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
Transparency of legal entity ownership through reporting Beneficial Owner (BO) to the Ministry of Law and Human Rights is an important policy in preventing Money Laundering. However, the practice of shadow controllers, parties who de facto control a legal entity but are not reported as BO, remains a serious loophole. Banks as gatekeepers of the financial system have a strategic position to detect shadow controllers. This article aims to analyze the legal liability of banks for failing to detect shadow controllers, the sanctions that may be imposed, and the standard of proof for constructive knowledge. This research uses normative legal method with statutory and conceptual approaches, examining the Banking Law (Law No. 7/1992 as amended by Law No. 4/2023 on P2SK), Anti-Money Laundering Law No. 8/2010, OJK Regulation No. 8/2023 on APU-PPT, and Ministry of Law Regulations No. 2/2025 and No. 49/2025 on corporate BO. The results show that bank liability is fault-based, not strict liability. Banks that ignore indications of shadow controllers may be subject to administrative sanctions (reprimands to license revocation), civil sanctions (damages claims), and criminal sanctions. The standard of proof for constructive knowledge uses objective indicators such as suspicious transactions, complex ownership structures, and discrepancies between official documents and customer operational reality, measured by the reasonableness principle (prudent banker). This article recommends that banks act proactively by conducting independent verification beyond merely relying on the Ministry's BO reports, and strengthen early detection systems against shadow controllers.